Pengaruh Kemampuan Akademik, Penghargaan Finansial, dan Risiko Profesi Terhadap Minat Mahasiswa Akuntansi Untuk Berkarier Sebagai Akuntan Publik: (Studi Pada Mahasiswa Jurusan Akuntansi Universitas Hindu Indonesia) - Jayanti, Ni Putu Risma; Putra, Cokorda Gde Bayu; Yuniasih, Ni Wayan (UNHI Press, 2025)
The disparity between the limited quantity of public accountants in Indonesia and the substantial annual output of accounting graduates, exceeding 35,000 students, underscores a pressing need for more professionals in this field. Given Indonesia's significant economic stature, the demand for public accountants is paramount to support the nation's economic growth. This research objective is to delve into the factors influencing accounting students' inclination towards pursuing a career as public accountants, particularly focusing on academic proficiency, financial incentives, and perceived professional risks. Conducted among students majoring in accounting at Hindu Indonesia University, this research targets active participants enrolled in the Undergraduate Study Program within the Department of Accounting, Faculty of Business Economics and Tourism, in their fifth and seventh semesters, who have completed audit I and audit II courses. With a sample size of 180 students, determined applying the Slovin formula, the study employs multiple linear regression analysis techniques to examine the relationships between the aforementioned variables and students' interest in embarking on a career as public accountants.The findings reveal that academic aptitude, financial rewards, and perceptions of professional risks positively impact Accounting Students' Interest in a Career as a Public Accountant